Preparation method of modified MoSi2 anti-oxidation coating on surface of molybdenum or molybdenum alloy

The Mo-Si-B-Hf-Y composite coating was prepared by a two-step molten salt non-electrolysis process, which solved the problems of insufficient density and poor antioxidant performance of the existing MoSi2 coating, and achieved efficient anti-oxidation of the coating Performance and durability meet the needs of molybdenum or molybdenum alloys in high-temperature service environments.

CN119433426APending Publication Date: 2025-02-14XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411557679.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing MoSi2 coating has defects such as insufficient density, unoptimized microstructure and internal cracks at high temperatures, resulting in insufficient oxidation resistance and durability, which cannot meet the requirements of molybdenum and molybdenum alloys in high-temperature service environments.

Method used

The Mo-Si-B-Hf-Y composite coating was prepared by a two-step molten salt non-electrolytic process. The powder was mixed by ball mill and dried to ensure that NaCl-KCl-NaF, Na2SiF6, Si, borax/B4C and HfB2 or Y were The uniform mixing and penetration of /Y2O3/YCl3 and other materials improves the density and oxidation resistance of the coating.

Benefits of technology

It significantly improves the oxidation resistance and durability of the coating, ensures the safe service of molybdenum or molybdenum alloy in high-temperature environments, and meets the application requirements in high-temperature service environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433426A_ABST
    Figure CN119433426A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal coatings, and particularly relates to a preparation method of a modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy, at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder and borax / B4C powder, at least one of HfB2 powder and Y / Y2O3 / YCl3 powder are selected, and a Mo-Si-B-Hf-Y composite coating is prepared on the surface of the molybdenum alloy through a two-step fused salt non-electrolytic process, moSi2 is used as a base material of the coating so that the oxidation resistance of the composite coating can be guaranteed, the oxidation resistance of the coating can be further improved by adding a proper amount of B element, Hf element and Y element, finally, good oxidation resistance, good compactness and durability of the coating are achieved, and application of molybdenum or molybdenum alloy in a high-temperature service environment can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal coating preparation, and specifically relates to a method for preparing a modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy. Background Art

[0002] As common refractory metals, molybdenum and molybdenum alloys are widely used in structural parts in high-temperature service environments in industries such as aerospace, metallurgy, chemical industry, and electronics because of their excellent properties such as high strength and hardness, high melting point, low thermal expansion coefficient, and good electrical and thermal conductivity at 1500°C. However, in high-temperature service environments, molybdenum and molybdenum alloys are very susceptible to oxidation, causing structural failure. Therefore, improving the oxidation resistance of molybdenum and molybdenum alloys is the key to ensuring their long-term safe service. At present, alloying and protective coating preparation methods are often used to improve the oxidation resistance of molybdenum and molybdenum alloys. Among them, the limited alloying of molybdenum alloys to improve their oxidation resistance cannot meet the increasingly stringent service requirements. Therefore, surface coatings are often used to improve the oxidation resistance of molybdenum and molybdenum alloys, thereby ensuring their safe service. MoSi2 coating reacts with O2 at high temperature to generate a stable SiO2 glass phase, and its low oxygen diffusion rate reduces the erosion rate of oxygen elements on the coating, so it is widely used in the design of anti-oxidation coatings on the surface of molybdenum and molybdenum alloys. However, due to the difference in thermal expansion coefficients between the coating and the substrate, the looseness of the coating, cracks inside the coating and other defects, it is necessary to modify and optimize it. Summary of the invention

[0003] In order to solve the problems existing in the prior art, the main purpose of the present invention is to propose a method for preparing a modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy, optimize the density and microstructure of the existing MoSi2 coating, realize the atomic penetration of Hf, Y, and B elements into the coating, and improve the anti-oxidation performance and durability of the coating.

[0004] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:

[0005] A method for preparing a powder for surface modification of molybdenum or molybdenum alloy comprises the following steps:

[0006] S1. Take at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax / B4C powder, HfB2 powder, Y / Y2O3 / YCl3 powder for standby;

[0007] S2. The NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, at least one of borax and B4C powder, and HfB2 powder were placed in a ball mill and mixed to obtain a mixed powder #1, the ball milling speed was 150 to 300 rpm, and the ball milling time was 1.5 to 3.5 h;

[0008] S3. The NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, at least one of borax / B4C powder, at least one of Y / Y2O3 / YCl3 powder was placed in a ball mill and mixed to obtain a 2# mixed powder, the ball milling speed was 150 to 300 rpm, and the ball milling time was 1.5 to 3.5 h;

[0009] S4. Place the 1# mixed powder and the 2# mixed powder in a dryer to dry them respectively, to obtain powders for surface modification of molybdenum or molybdenum alloy.

[0010] As a preferred embodiment of the method for preparing the powder for surface modification of molybdenum or molybdenum alloy according to the present invention, before step S1, the method further comprises:

[0011] S0. Use a grinding mortar to grind at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax / B4C powder, HfB2 powder, and Y / Y2O3 / YCl3 powder.

[0012] As a preferred embodiment of the method for preparing the powder for surface modification of molybdenum or molybdenum alloy described in the present invention, wherein: in the step S1, the particle size of at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax / B4C powder, HfB2 powder, and Y / Y2O3 / YCl3 powder is 3 to 60 μm.

[0013] As a preferred embodiment of the method for preparing the powder for surface modification of molybdenum or molybdenum alloy according to the present invention, in the steps S2 and S3, the ball milling is performed in forward and reverse directions, and the forward and reverse directions are performed for the same time.

[0014] As a preferred embodiment of the method for preparing the powder for surface modification of molybdenum or molybdenum alloy described in the present invention, wherein: in the step S4, in the 1# mixed powder for surface modification of molybdenum or molybdenum alloy, the content of NaCl-KCl-NaF powder is 35-94.7wt%, the content of Na2SiF6 powder is 0.1-20wt%, the content of Si powder is 5-20wt%, the content of at least one of borax and B4C powder is 0.1-10wt%, and the content of HfB2 powder is 0.1-15wt%; in the 2# mixed powder for surface modification of molybdenum or molybdenum alloy, the content of NaCl-KCl-NaF powder is 30-94.7wt%, the content of Na2SiF6 powder is 0.1-20wt%, the content of Si powder is 5-20wt%, the content of at least one of borax and B4C powder is 0.1-10wt%, and the content of at least one of Y / Y2O3 / YCl3 powder is 0.1-20wt%.

[0015] A powder for surface modification of molybdenum or molybdenum alloy is prepared by the above-mentioned method for preparing the powder for surface modification of molybdenum or molybdenum alloy.

[0016] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:

[0017] A method for preparing a modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy comprises the following steps:

[0018] B1. embedding a molybdenum or molybdenum alloy matrix into the 1# mixed powder or 2# mixed powder in the above-mentioned powder for surface modification of molybdenum or molybdenum alloy;

[0019] B2. Controlling the heating temperature and heating time to obtain a pre-treated coating sample of a molten salt non-electrolytic modified coating on the surface of molybdenum or molybdenum alloy;

[0020] B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating into another mixed powder of the above-mentioned powder for surface modification of molybdenum or molybdenum alloy;

[0021] B4. Control the heating temperature and heating time to obtain a two-step molten salt non-electrolytic modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy.

[0022] As a preferred embodiment of the method for preparing the modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy according to the present invention, the method further comprises: before step B1,

[0023] B0. Use sandpaper to grind the molybdenum or molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for use.

[0024] As a preferred embodiment of the method for preparing the modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy described in the present invention, wherein: in the steps B1 and B3, the thickness of the powder used for surface modification of molybdenum or molybdenum alloy covering the molybdenum or molybdenum alloy substrate is ≥3 mm.

[0025] As a preferred embodiment of the method for preparing the modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy described in the present invention, wherein: in the steps B2 and B4, the heating temperature is 850-1100°C and the heating time is 2-8h.

[0026] The beneficial effects of the present invention are as follows:

[0027] The present invention proposes a method for preparing a modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy, wherein at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax and B4C powder, and HfB2 powder are selected. At least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax and B4C powder, and at least one of Y / Y2O3 / YCl3 powder are selected. A Mo-Si-B-Hf-Y composite coating is prepared on the surface of a molybdenum alloy by a two-step molten salt non-electrolytic process, wherein MoSi2 as the basic material of the coating can ensure the anti-oxidation performance of the composite coating, and adding an appropriate amount of B element, Hf element and Y element can further improve the anti-oxidation performance of the coating, and finally the coating has good anti-oxidation performance, good density and durability, which can meet the application of molybdenum or molybdenum alloy in high-temperature service environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0029] Figure 1 It is a schematic diagram of molybdenum or molybdenum alloy having a modified coating on the surface of the present invention.

[0030] Figure 2 This is a cross-sectional SEM image of the coating of Example 6 of the present invention.

[0031] Figure 3 This is the cross-sectional EDS characterization of the coating of Example 6 of the present invention.

[0032] Figure 4 This is a cross-sectional SEM image of the coating of Example 12 of the present invention.

[0033] Figure 5 This is the cross-sectional EDS characterization of the coating of Example 12 of the present invention.

[0034] Figure 6 This is a cross-sectional SEM image of the coating of Comparative Example 3 of the present invention.

[0035] Figure 7 This is the cross-sectional EDS characterization of the coating of Comparative Example 3 of the present invention.

[0036] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0037] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The present invention provides a method for preparing a modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy, optimizes the density and microstructure of the existing MoSi2 coating, realizes the atomic penetration of Hf, Y and B elements into the coating, and improves the anti-oxidation performance and durability of the coating.

[0039] According to one aspect of the present invention, the present invention provides the following technical solution:

[0040] A method for preparing a modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy comprises the following steps:

[0041] B1. Embedding a molybdenum or molybdenum alloy matrix in a 1# mixed powder or a 2# mixed powder in a powder for surface modification of molybdenum or molybdenum alloy; in the 1# mixed powder: the content of NaCl-KCl-NaF powder is 35-94.7wt%, the content of Na2SiF6 powder is 0.1-20wt%, the content of Si powder is 5-20wt%, the content of at least one of borax and B4C powder is 0.1-10wt%, and the content of HfB2 powder is 0.1-15wt%; specifically, the content of NaCl-KCl-NaF powder can be, for example, but not limited to, any one of 35wt%, 45wt%, 55wt%, 65wt%, 75wt%, 85wt%, 95wt% or the range between any two thereof; the content of Na2SiF6 powder can be, for example, but not limited to, 0.1wt%, 1wt%, 2wt%, 5wt%, 10wt% , 15wt%, 20wt% or any range between any two of them; the content of at least one of borax and B4C powder can be, for example but not limited to, 0.1wt%, 1wt%, 2wt%, 5wt%, 10wt% or any range between any two of them; the content of HfB2 powder can be, for example but not limited to, 0.1wt%, 1wt%, 2wt%, 5wt%, 10wt%, 15wt% or any range between any two of them; in 2# mixed powder: the content of NaCl-KCl-NaF powder is 30-94.7wt%, the content of Na2SiF6 powder is 0.1-20wt%, the content of Si powder is 5-20wt%, the content of at least one of borax and B4C powder is 0.1-10wt%, and the content of at least one of Y / Y2O3 / YCl3 powder is 0.1-20wt%. Specifically, the content of NaCl-KCl-NaF powder can be, for example, but not limited to, any one of 30wt%, 40wt%, 55wt%, 65wt%, 75wt%, 85wt%, 95wt% or any range between two of them; the content of Na2SiF6 powder can be, for example, but not limited to, any one of 0.1wt%, 1wt%, 2wt%, 5wt%, 10wt%, 15wt%, 20wt% or any range between two of them; the content of at least one of borax and B4C powder can be, for example, but not limited to, any one of 0.1wt%, 1wt%, 2wt%, 5wt%, 10wt% or any range between two of them; the content of at least one of Y / Y2O3 / YCl3 powder can be, for example, but not limited to, any one of 0.1wt%, 1wt%, 2wt%, 5wt%, 10wt%, 20wt% or any range between two of them;

[0042] B2. Controlling the heating temperature and heating time to obtain a pre-treated coating sample of a molten salt non-electrolytic modified coating on the surface of molybdenum or molybdenum alloy;

[0043] B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating into another mixed powder of the above-mentioned powder for surface modification of molybdenum or molybdenum alloy;

[0044] B4. Control the heating temperature and heating time to obtain a two-step molten salt non-electrolytic modified coating on the surface of molybdenum or molybdenum alloy. The molybdenum or molybdenum alloy having the modified coating on the surface is as follows: Figure 1 As shown, the surface of the two-step molten salt non-electrolytic modified coating on the surface of molybdenum or molybdenum alloy is smooth and has no obvious macroscopic defects.

[0045] Preferably, before step B1, the method further includes:

[0046] B0. The molybdenum or molybdenum alloy substrate is polished with sandpaper, then cleaned with anhydrous ethanol, and then dried for standby use. The sandpaper is 400-2000 mesh sandpaper, and sandpapers of different meshes are selected in turn for polishing according to needs.

[0047] Preferably, in steps B1 and B3, the thickness of the powder for surface modification of molybdenum or molybdenum alloy covered on the molybdenum or molybdenum alloy substrate is ≥3 mm, and the molybdenum alloy is a molybdenum alloy commonly used in the art, such as Mo-Zr-C molybdenum alloy.

[0048] Preferably, in the steps B2 and B4, a muffle furnace / tube furnace is used, a thermocouple is used as a heat source, the heating temperature is controlled to be 850-1100°C, the heating time is 2-8h, and the powder for surface modification of molybdenum or molybdenum alloy is prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method. Specifically, the heating temperature can be, for example, but not limited to, any one of 850°C, 900°C, 950°C, 1000°C, 1100°C, or a range between any two thereof; the heating time can be, for example, but not limited to, any one of 2h, 3h, 4h, 5h, 6h, 7h, 8h, or a range between any two thereof.

[0049] Preferably, the method for preparing the powder for surface modification of molybdenum or molybdenum alloy comprises the following steps:

[0050] S1. Take at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax and B4C powder, HfB2 powder, and Y / Y2O3 / YCl3 powder for standby;

[0051] S2. The NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, at least one of borax and B4C powder, and HfB2 powder were placed in a ball mill and mixed to obtain a mixed powder #1, the ball milling speed was 150 to 300 rpm, and the ball milling time was 1.5 to 3.5 h;

[0052] S3. The NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, at least one of borax / B4C powder, at least one of Y / Y2O3 / YCl3 powder was placed in a ball mill and mixed to obtain a 2# mixed powder, the ball milling speed was 150 to 300 rpm, and the ball milling time was 1.5 to 3.5 h;

[0053] S4. Place the 1# mixed powder and the 2# mixed powder in a dryer to dry them respectively to obtain powders for surface modification of molybdenum or molybdenum alloy.

[0054] Preferably, before step S1, the method further includes:

[0055] S0. Use a grinding mortar to grind at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax and B4C powder, HfB2 powder, and Y / Y2O3 / YCl3 powder.

[0056] Preferably, in step S1, the particle sizes of at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax and B4C powder, HfB2 powder and Y / Y2O3 / YCl3 powder are all 3 to 60 μm. Specifically, the particle sizes of at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax and B4C powder, HfB2 powder and Y / Y2O3 / YCl3 powder can be, for example but not limited to, any one of 3 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm or any two thereof;

[0057] Preferably, in steps S2 and S3, the ball milling speed may be, for example but not limited to, any one of 150rpm, 160rpm, 170rpm, 180rpm, 190rpm, 200rpm, 210rpm, 220rpm, 230rpm, 240rpm, 250rpm, 260rpm, 270rpm, 280rpm, 290rpm, and 300rpm, or a range between any two of them; the ball milling time may be, for example but not limited to, any one of 1h30min, 1h45min, 2h, 2h15min, 2h30min, 2h45min, 3h, 3h15min, and 3h30min, or a range between any two of them; further preferably, the forward and reverse rotation during ball milling may be performed by first performing forward rotation for half of the ball milling time and then performing reverse rotation for the other half of the ball milling time; or may be performed by first performing forward rotation for a certain period of time and then performing reverse rotation for the same period of time, then performing forward rotation for a certain period of time and then performing reverse rotation for the same period of time, until the ball milling is completed.

[0058] Preferably, in step S4, the drying may be carried out by a conventional drying method in the art.

[0059] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0060] Example 1

[0061] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum surface comprises the following steps:

[0062] B0. Use 400-2000 mesh sandpaper to grind the molybdenum substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0063] S0. NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders were ground using a grinding mortar;

[0064] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders are all 3 to 60 μm;

[0065] S2. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders were placed in a ball mill and mixed to obtain 1# mixed powder. The ball milling speed was 150 rpm, the ball milling time was 3.5 h, and the forward and reverse rotations were 1.75 h each;

[0066] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and Y powders were placed in a ball mill and mixed to obtain 2# mixed powder. The ball milling speed was 150 rpm, the ball milling time was 3.5 h, and the forward and reverse rotations were 1.75 h each;

[0067] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 67.9wt%, the content of Na2SiF6 powder is 2wt%, the content of Si powder is 15wt%, the total content of borax and B4C powder is 0.1wt%, and the content of HfB2 powder is 15wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 70wt%, the content of Na2SiF6 powder is 5wt%, the content of Si powder is 5wt%, the total content of borax and B4C powder is 5wt%, and the content of Y powder is 15wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for molybdenum surface modification.

[0068] B1, burying the molybdenum substrate in the 1# mixed powder for molybdenum surface modification described in S4; the thickness of the powder for molybdenum surface modification covering the molybdenum substrate is 3 mm;

[0069] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 850°C, and the heating time was 8 hours. The 1# mixed powder for molybdenum surface modification was prepared on a molybdenum substrate by a molten salt non-electrolytic method, and a pre-treated coating sample of the molten salt non-electrolytic method modified coating was obtained on the molybdenum surface.

[0070] B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating in the 2# mixed powder; the thickness of the powder for molybdenum surface modification covering the pre-treated coating sample is 3 mm;

[0071] B4. Using a muffle furnace and a thermocouple as a heat source, the heating temperature is controlled to be 850°C and the heating time is 8 hours. The 2# mixed powder for molybdenum surface modification is prepared on a molybdenum substrate by a molten salt non-electrolytic method to obtain a two-step molten salt non-electrolytic modified coating on the molybdenum surface.

[0072] Example 2

[0073] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0074] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0075] S0. NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders were ground using a grinding mortar;

[0076] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders are all 3 to 60 μm;

[0077] S2. Place NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders in a ball mill and mix them to obtain 1# mixed powder. The ball milling speed is 200 rpm, the ball milling time is 2 h, and the forward and reverse rotations are 1 h each;

[0078] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and Y powders were placed in a ball mill and milled to obtain a 2# mixed powder. The ball milling speed was 200 rpm, the ball milling time was 2 h, and the forward and reverse rotations were 1 h each;

[0079] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 56wt%, the content of Na2SiF6 powder is 10wt%, the content of Si powder is 20wt%, the total content of borax and B4C powder is 4wt%, and the content of HfB2 powder is 10wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 79.9wt%, the content of Na2SiF6 powder is 5wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 5wt%, and the content of Y powder is 0.1wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for surface modification of molybdenum alloy.

[0080] B1. The molybdenum alloy matrix is ​​buried in the 1# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the molybdenum alloy matrix is ​​4 mm;

[0081] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 1100° C., and the heating time was 2 h. The 1# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a pre-treated coating sample of the molten salt non-electrolytic method modified coating was obtained on the surface of the molybdenum alloy.

[0082] B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating in the 2# mixed powder; the thickness of the powder for surface modification of molybdenum alloy covering the pre-treated coating sample is 4 mm;

[0083] B4. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 1100° C., and the heating time was 2 h. The 2# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a two-step molten salt non-electrolytic modified coating was obtained on the surface of the molybdenum alloy.

[0084] Example 3

[0085] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum surface comprises the following steps:

[0086] B0. Use 400-2000 mesh sandpaper to grind the molybdenum substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0087] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders using a grinding mortar;

[0088] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders are all 3 to 60 μm;

[0089] S2. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders were placed in a ball mill and mixed to obtain 1# mixed powder. The ball milling speed was 300 rpm, the ball milling time was 1.5 h, and the forward and reverse rotations were 0.75 h each;

[0090] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and Y2O3 powders were placed in a ball mill and mixed to obtain 2# mixed powder. The ball milling speed was 300 rpm, the ball milling time was 1.5 h, and the forward and reverse rotations were 0.75 h each;

[0091] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 62wt%, the content of Na2SiF6 powder is 20wt%, the content of Si powder is 5wt%, the total content of borax and B4C powder is 8wt%, and the content of HfB2 powder is 5wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 59.9wt%, the content of Na2SiF6 powder is 10wt%, the content of Si powder is 20wt%, the total content of borax and B4C powder is 0.1wt%, and the content of Y2O3 powder is 10wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for molybdenum surface modification.

[0092] B1. The molybdenum matrix is ​​buried in the 1# mixed powder; the thickness of the powder for molybdenum surface modification covering the molybdenum matrix is ​​4 mm;

[0093] B2. A tubular furnace is used with a heating element as a heat source, the heating temperature is controlled to be 950° C., and the heating time is 2 hours. The 1# mixed powder for molybdenum surface modification is prepared on a molybdenum substrate by a molten salt non-electrolytic method to obtain a pretreated coating sample of a molten salt non-electrolytic modified coating on the molybdenum surface.

[0094] B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating in the 2# mixed powder; the thickness of the powder for molybdenum surface modification covering the pre-treated coating sample is 3 mm;

[0095] B4. Using a tubular furnace and a heating element as a heat source, the heating temperature is controlled to be 1050°C and the heating time is 4 hours. The 2# mixed powder for molybdenum surface modification is prepared on a molybdenum substrate by a molten salt non-electrolytic method to obtain a two-step molten salt non-electrolytic modified coating on the molybdenum surface.

[0096] Example 4

[0097] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0098] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0099] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders using a grinding mortar;

[0100] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders are all 3 to 60 μm;

[0101] S2. Place NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders in a ball mill and mix them to obtain 1# mixed powder. The ball milling speed is 150 rpm, the ball milling time is 2 h, and the forward and reverse rotations are 1 h each;

[0102] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and Y2O3 powders were placed in a ball mill and mixed to obtain 2# mixed powder. The ball milling speed was 200 rpm, the ball milling time was 3 h, and the forward and reverse rotations were 1.5 h each;

[0103] In S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 67wt%, the content of Na2SiF6 powder is 12.9wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 10wt%, and the content of HfB2 powder is 0.1wt%. In 2# mixed powder, the content of NaCl-KCl-NaF powder is 65wt%, the content of Na2SiF6 powder is 15wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 5wt%, and the content of Y2O3 powder is 5wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for surface modification of molybdenum alloys;

[0104] B1, mixing the molybdenum alloy matrix 1# with the mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the molybdenum alloy matrix is ​​4.5 mm;

[0105] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 950° C., and the heating time was 4 hours. The 1# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a pre-treated coating sample of the molten salt non-electrolytic method modified coating was obtained on the surface of the molybdenum alloy.

[0106] B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating in the 2# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the pre-treated coating sample is 4 mm;

[0107] B4. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 1050°C, and the heating time was 6 hours. The 2# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a two-step molten salt non-electrolytic modified coating was obtained on the surface of the molybdenum alloy.

[0108] Example 5

[0109] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0110] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0111] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders using a grinding mortar;

[0112] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders are all 3 to 60 μm;

[0113] S2. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders were placed in a ball mill and milled to obtain a mixed powder. The ball milling speed was 300 rpm, the ball milling time was 3 h, and the forward and reverse rotations were 1.5 h each;

[0114] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and YCl3 powders were placed in a ball mill and milled to obtain a mixed powder. The ball milling speed was 150 rpm, the ball milling time was 2 h, and the forward and reverse rotations were 1 h each;

[0115] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 85.7wt%, the content of Na2SiF6 powder is 0.1wt%, the content of Si powder is 5wt%, the total content of borax and B4C powder is 4.2wt%, and the content of HfB2 powder is 5wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 55wt%, the content of Na2SiF6 powder is 15wt%, the content of Si powder is 5wt%, the total content of borax and B4C powder is 5wt%, and the content of YCl3 powder is 20wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for surface modification of molybdenum alloy.

[0116] B1. The molybdenum alloy matrix is ​​buried in the 1# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the molybdenum alloy matrix is ​​3 mm;

[0117] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 1000° C., and the heating time was 6 hours. The 1# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a pre-treated coating sample of the molten salt non-electrolytic method modified coating was obtained on the surface of the molybdenum alloy.

[0118] B3. The pre-treated coating sample of the molten salt non-electrolytic modified coating is buried in the 2# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the pre-treated coating sample is 5 mm;

[0119] B4. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 950° C., and the heating time was 6 hours. The 2# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a two-step molten salt non-electrolytic modified coating was obtained on the surface of the molybdenum alloy.

[0120] Example 6

[0121] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0122] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0123] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders using a grinding mortar;

[0124] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders are all 3 to 60 μm;

[0125] S2. Place NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders in a ball mill and mix them to obtain 1# mixed powder. The ball milling speed is 200 rpm, the ball milling time is 2 h, and the forward and reverse rotations are 1 h each;

[0126] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and YCl3 powders were placed in a ball mill and mixed to obtain 2# mixed powder. The ball milling speed was 200 rpm, the ball milling time was 2h, and the forward and reverse rotations were 1h each;

[0127] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 63wt%, the content of Na2SiF6 powder is 15wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 2wt%, and the content of HfB2 powder is 10wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 60wt%, the content of Na2SiF6 powder is 10wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 10wt%, and the content of YCl3 powder is 10wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for surface modification of molybdenum alloy.

[0128] B1. The molybdenum alloy matrix is ​​buried in the 1# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the molybdenum alloy matrix is ​​3 mm;

[0129] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 1000° C., and the heating time was 4 hours. The 1# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a pre-treated coating sample of the molten salt non-electrolytic method modified coating was obtained on the surface of the molybdenum alloy.

[0130] B3. The pre-treated coating sample of the molten salt non-electrolytic modified coating is buried in the 2# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the pre-treated coating sample is 3 mm;

[0131] B4, using a muffle furnace, a thermocouple as a heat source, controlling the heating temperature to 1000°C, and the heating time to 4 hours, the 2# mixed powder for surface modification of molybdenum alloy is prepared on the molybdenum alloy substrate by molten salt non-electrolytic method, and a two-step molten salt non-electrolytic modified coating is obtained on the surface of the molybdenum alloy. The cross-sectional SEM image is as follows Figure 2 As shown, its cross-sectional EDS characterization is as follows Figure 3 As shown in the figure, no obvious micro cracks were observed inside the coating, the microstructure was fine, and the interface bonding was good. Si, B, Hf, and Y elements had obvious distribution in the EDS characterization diagram, indicating that the Mo-Si-B-Hf-Y coating had been successfully prepared.

[0132] Example 7

[0133] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0134] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0135] S0. NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders were ground using a grinding mortar;

[0136] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders are all 3 to 60 μm;

[0137] S2. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders were placed in a ball mill and mixed to obtain 1# mixed powder. The ball milling speed was 150 rpm, the ball milling time was 1.5 h, and the forward and reverse rotations were 0.75 h each;

[0138] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and Y powders were placed in a ball mill and mixed to obtain 2# mixed powder. The ball milling speed was 150 rpm, the ball milling time was 3.5 h, and the forward and reverse rotations were 1.75 h each;

[0139] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 61wt%, the content of Na2SiF6 powder is 15wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 4wt%, and the content of HfB2 powder is 10wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 63wt%, the content of Na2SiF6 powder is 20wt%, the content of Si powder is 5wt%, the total content of borax and B4C powder is 2wt%, and the content of Y powder is 10wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for surface modification of molybdenum alloy.

[0140] B1. The molybdenum alloy matrix is ​​buried in the 2# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the molybdenum alloy matrix is ​​4 mm;

[0141] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 850°C, and the heating time was 8 hours. The 2# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a pre-treated coating sample of a molten salt non-electrolytic modified coating was obtained on the surface of the molybdenum alloy.

[0142] B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating in the 1# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the pre-treated coating sample is 4 mm;

[0143] B4. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 850° C., and the heating time was 8 hours. The 1# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a two-step molten salt non-electrolytic modified coating was obtained on the surface of the molybdenum alloy.

[0144] Example 8

[0145] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0146] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0147] S0. NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders were ground using a grinding mortar;

[0148] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders are all 3 to 60 μm;

[0149] S2. Place NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders in a ball mill and mix them to obtain 1# mixed powder. The ball milling speed is 200 rpm, the ball milling time is 2 h, and the forward and reverse rotations are 1 h each;

[0150] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and Y powders were placed in a ball mill and milled to obtain a 2# mixed powder. The ball milling speed was 200 rpm, the ball milling time was 2 h, and the forward and reverse rotations were 1 h each;

[0151] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 73wt%, the content of Na2SiF6 powder is 10wt%, the content of Si powder is 5wt%, the total content of borax and B4C powder is 2wt%, and the content of HfB2 powder is 10wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 71.9wt%, the content of Na2SiF6 powder is 0.1wt%, the content of Si powder is 15wt%, the total content of borax and B4C powder is 8wt%, and the content of Y powder is 5wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for surface modification of molybdenum alloy.

[0152] B1. The molybdenum alloy matrix is ​​buried in the 2# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the molybdenum alloy matrix is ​​3.5 mm;

[0153] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 1100° C., and the heating time was 2 h. The 2# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a pre-treated coating sample of the molten salt non-electrolytic method modified coating was obtained on the surface of the molybdenum alloy.

[0154] B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating in the 1# mixed powder; the thickness of the powder for surface modification of molybdenum alloy covering the pre-treated coating sample is 4.5 mm;

[0155] B4. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 1100° C., and the heating time was 2 h. The 1# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a two-step molten salt non-electrolytic modified coating was obtained on the surface of the molybdenum alloy.

[0156] Example 9

[0157] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0158] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0159] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders using a grinding mortar;

[0160] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders are all 3 to 60 μm;

[0161] S2. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders were placed in a ball mill and mixed to obtain 1# mixed powder. The ball milling speed was 300 rpm, the ball milling time was 3 h, and the forward and reverse rotations were 1.5 h each;

[0162] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and Y2O3 powders were placed in a ball mill and mixed to obtain 2# mixed powder. The ball milling speed was 300 rpm, the ball milling time was 3 h, and the forward and reverse rotations were 1.5 h each;

[0163] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 60wt%, the content of Na2SiF6 powder is 15wt%, the content of Si powder is 15wt%, the total content of borax and B4C powder is 5wt%, and the content of HfB2 powder is 5wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 67wt%, the content of Na2SiF6 powder is 10wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 5wt%, and the content of Y2O3 powder is 8wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for surface modification of molybdenum alloy.

[0164] B1. The molybdenum alloy matrix is ​​buried in the 2# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the molybdenum alloy matrix is ​​4 mm;

[0165] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 950° C., and the heating time was 2 h. The 2# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a pretreatment coating sample of a molten salt non-electrolytic modified coating was obtained on the surface of the molybdenum alloy.

[0166] B3. The pre-treated coating sample of the molten salt non-electrolytic modified coating is buried in the 1# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the pre-treated coating sample is 5 mm;

[0167] B4. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 1050° C., and the heating time was 4 hours. The 1# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a two-step molten salt non-electrolytic modified coating was obtained on the surface of the molybdenum alloy.

[0168] Example 10

[0169] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0170] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0171] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders using a grinding mortar;

[0172] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders are all 3 to 60 μm;

[0173] S2. Place NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders in a ball mill and mix them to obtain 1# mixed powder. The ball milling speed is 150 rpm, the ball milling time is 2 h, and the forward and reverse rotations are 1 h each;

[0174] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and Y2O3 powders were placed in a ball mill and mixed to obtain 2# mixed powder. The ball milling speed was 200 rpm, the ball milling time was 1.5 h, and the forward and reverse rotations were 0.75 h each;

[0175] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 74wt%, the content of Na2SiF6 powder is 5wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 6wt%, and the content of HfB2 powder is 5wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 50wt%, the content of Na2SiF6 powder is 10wt%, the content of Si powder is 15wt%, the total content of borax and B4C powder is 10wt%, and the content of Y2O3 powder is 15wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for surface modification of molybdenum alloy.

[0176] B1. The molybdenum alloy matrix is ​​buried in the 2# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the molybdenum alloy matrix is ​​5 mm;

[0177] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 950° C., and the heating time was 4 hours. The 2# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a pretreatment coating sample of the molten salt non-electrolytic method modified coating was obtained on the surface of the molybdenum alloy.

[0178] B3. The pre-treated coating sample of the molten salt non-electrolytic modified coating is buried in the 1# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the pre-treated coating sample is 5.5 mm;

[0179] B4. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 1050° C., and the heating time was 6 hours. The 1# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a two-step molten salt non-electrolytic modified coating was obtained on the surface of the molybdenum alloy.

[0180] Embodiment 11

[0181] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0182] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0183] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders using a grinding mortar;

[0184] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders are all 3 to 60 μm;

[0185] S2. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders were placed in a ball mill and mixed to obtain 1# mixed powder. The ball milling speed was 300 rpm, the ball milling time was 3 h, and the forward and reverse rotations were 1.5 h each;

[0186] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and YCl3 powders were placed in a ball mill and mixed to obtain 2# mixed powder. The ball milling speed was 150 rpm, the ball milling time was 2 h, and the forward and reverse rotations were 1 h each;

[0187] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 76wt%, the content of Na2SiF6 powder is 5wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 4wt%, and the content of HfB2 powder is 5wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 57wt%, the content of Na2SiF6 powder is 5wt%, the content of Si powder is 15wt%, the total content of borax and B4C powder is 8wt%, and the content of YCl3 powder is 15wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for surface modification of molybdenum alloy.

[0188] B1. The molybdenum alloy matrix is ​​buried in the 2# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the molybdenum alloy matrix is ​​4 mm;

[0189] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 1000° C., and the heating time was 6 hours. The 2# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a pretreatment coating sample of the molten salt non-electrolytic method modified coating was obtained on the surface of the molybdenum alloy.

[0190] B3. The pre-treated coating sample of the molten salt non-electrolytic modified coating is buried in the 1# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the pre-treated coating sample is 5 mm;

[0191] B4. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 950° C., and the heating time was 6 hours. The 1# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a two-step molten salt non-electrolytic modified coating was obtained on the surface of the molybdenum alloy.

[0192] Example 12

[0193] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0194] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0195] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders using a grinding mortar;

[0196] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders are all 3 to 60 μm;

[0197] S2. Place NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders in a ball mill and mix them to obtain 1# mixed powder. The ball milling speed is 200 rpm, the ball milling time is 2 h, and the forward and reverse rotations are 1 h each;

[0198] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and YCl3 powders were placed in a ball mill and mixed to obtain 2# mixed powder. The ball milling speed was 200 rpm, the ball milling time was 2h, and the forward and reverse rotations were 1h each;

[0199] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 68wt%, the content of Na2SiF6 powder is 10wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 2wt%, and the content of HfB2 powder is 10wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 60wt%, the content of Na2SiF6 powder is 10wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 10wt%, and the content of YCl3 powder is 10wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for surface modification of molybdenum alloy.

[0200] B1. The molybdenum alloy matrix is ​​buried in the 2# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the molybdenum alloy matrix is ​​3.5 mm;

[0201] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 1000° C., and the heating time was 4 hours. The 2# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a pre-treated coating sample of the molten salt non-electrolytic method modified coating was obtained on the surface of the molybdenum alloy.

[0202] B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating in the 1# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the pre-treated coating sample is 4 mm;

[0203] B4, using a muffle furnace, a thermocouple as a heat source, controlling the heating temperature to 1000°C, and the heating time to 4 hours, the 1# mixed powder for surface modification of molybdenum alloy is prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a two-step molten salt non-electrolytic modified coating is obtained on the surface of the molybdenum alloy. The cross-sectional SEM image is as follows Figure 4 As shown, its cross-sectional EDS characterization is as follows Figure 5 As shown in the figure, no obvious micro cracks were observed inside the coating, the microstructure was fine, and the interface bonding was good. Si, B, Hf, and Y elements had obvious distribution in the EDS characterization diagram, indicating that the Mo-Si-B-Hf-Y coating had been successfully prepared.

[0204] Comparative Example 1

[0205] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum surface comprises the following steps:

[0206] B0. Use 400-2000 mesh sandpaper to grind the molybdenum substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0207] B1. The molybdenum substrate is buried in the above-mentioned powder for surface modification of molybdenum or molybdenum alloy; the thickness of the powder for surface modification of molybdenum covering the molybdenum substrate is 4 mm; the powder for surface modification of molybdenum is prepared by the following method:

[0208] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si powders using a grinding mortar;

[0209] S1. Take NaCl-KCl-NaF, Na2SiF6, and Si powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, and Si powders are all 3 to 60 μm;

[0210] S2. The NaCl-KCl-NaF, Na2SiF6 and Si powders were placed in a ball mill and mixed to obtain a mixed powder. The ball milling speed was 300 rpm, the ball milling time was 1.5 h, and the forward and reverse rotations were 0.75 h each;

[0211] S3. The mixed powder is placed in a dryer and dried to obtain a powder for molybdenum surface modification, wherein the content of NaCl-KCl-NaF powder is 80wt%, the content of Na2SiF6 powder is 10wt%, and the content of Si powder is 10wt%.

[0212] B2. A muffle furnace is used with a thermocouple as a heat source, the heating temperature is controlled to be 850°C, and the heating time is 5 hours. The powder for surface modification of molybdenum is prepared on a molybdenum substrate by a molten salt non-electrolytic method, and a molten salt non-electrolytic MoSi2 coating is obtained on the molybdenum surface. Anti-oxidation experiments show that the severe oxidation temperature is lower than 1500°C.

[0213] Comparative Example 2

[0214] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0215] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0216] B1. The molybdenum alloy substrate is buried in the above-mentioned powder for surface modification of molybdenum or molybdenum alloy; the thickness of the powder for surface modification of molybdenum alloy covered on the molybdenum alloy substrate is 3 mm; the powder for surface modification of molybdenum alloy is prepared by the following method:

[0217] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C powder using a grinding mortar;

[0218] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, and B4C powder for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, and B4C powders are all 3 to 60 μm;

[0219] S2. The NaCl-KCl-NaF, Na2SiF6, Si, borax and B4C powders were placed in a ball mill and mixed to obtain a mixed powder. The ball milling speed was 250 rpm, the ball milling time was 3 h, and the forward and reverse rotations were 1.5 h each;

[0220] S3. The mixed powder is placed in a dryer and dried to obtain a powder for surface modification of molybdenum alloy, wherein the content of NaCl-KCl-NaF powder is 73wt%, the content of Na2SiF6 powder is 2wt%, the content of Si powder is 15wt%, and the total content of borax and B4C powder is 10wt%.

[0221] B2. A muffle furnace is used with a thermocouple as a heat source, the heating temperature is controlled to be 900°C, and the heating time is 4 hours. The powder for surface modification of the molybdenum alloy is prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a molten salt non-electrolytic method B modified coating is obtained on the surface of the molybdenum alloy. The oxidation resistance temperature is low, less than 1500°C.

[0222] Comparative Example 3

[0223] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0224] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0225] B1. The molybdenum alloy substrate is buried in the above-mentioned powder for surface modification of molybdenum or molybdenum alloy; the thickness of the powder for surface modification of molybdenum alloy covered on the molybdenum alloy substrate is 3.5 mm; the powder for surface modification of molybdenum alloy is prepared by the following method:

[0226] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and YCl3 powders using a grinding mortar;

[0227] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and YCl3 powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and YCl3 powders are all 3 to 60 μm;

[0228] S2. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and YCl3 powders were placed in a ball mill and mixed to obtain a mixed powder. The ball milling speed was 200 rpm, the ball milling time was 2 h, and the forward and reverse rotations were 1 h each;

[0229] S3. The mixed powder is placed in a dryer and dried to obtain a powder for surface modification of molybdenum alloy, wherein the content of NaCl-KCl-NaF powder is 60wt%, the content of Na2SiF6 powder is 10wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 10wt%, and the content of YCl3 powder is 10wt%.

[0230] B2. Using a muffle furnace, a thermocouple as a heat source, and controlling the heating temperature to 1000°C for 4 hours, the powder for surface modification of molybdenum alloy is prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method. The cross-sectional SEM image is shown in FIG. Figure 6 As shown in Figure 1, the prepared B and Y modified MoSi2 coatings are discontinuous, uneven in thickness, and have cracks. The cross-sectional EDS characterization is shown in Figure 1. Figure 7 As shown, the distribution of B and Y elements in the EDS characterization diagram is not obvious, and the coating needs to be further optimized.

[0231] Comparative Example 4

[0232] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0233] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0234] B1. The molybdenum alloy substrate is buried in the above-mentioned powder for surface modification of molybdenum or molybdenum alloy; the thickness of the powder for surface modification of molybdenum alloy covered on the molybdenum alloy substrate is 5 mm; the powder for surface modification of molybdenum alloy is prepared by the following method:

[0235] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders using a grinding mortar;

[0236] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders are all 3 to 60 μm;

[0237] S2. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders were placed in a ball mill and milled to obtain a mixed powder. The ball milling speed was 150 rpm, the ball milling time was 2 h, and the forward and reverse rotations were 1 h each;

[0238] S3. The mixed powder is placed in a dryer and dried to obtain a powder for surface modification of molybdenum alloy, wherein the content of NaCl-KCl-NaF powder is 50wt%, the content of Na2SiF6 powder is 10wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 10wt%, and the content of HfB2 powder is 20wt%.

[0239] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 900°C, and the heating time was 6 hours. The powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method. The study found that as the content of borax, B4C, and HfB2 continued to increase, the fluidity of the molten salt was poor and the coating was difficult to form.

[0240] Comparative Example 5

[0241] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0242] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0243] S0. NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders were ground using a grinding mortar;

[0244] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders are all 3 to 60 μm;

[0245] S2. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders were placed in a ball mill and milled to obtain a mixed powder #1. The ball milling speed was 200 rpm, the ball milling time was 3 h, and the forward and reverse rotations were 1.5 h each.

[0246] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and Y powders were placed in a ball mill and mixed to obtain 2# mixed powder. The ball milling speed was 150 rpm, the ball milling time was 2 h, and the forward and reverse rotations were 1 h each;

[0247] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 79.96wt%, the content of Na2SiF6 powder is 10wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 0.02wt%, and the content of HfB2 powder is 0.02wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 89.96wt%, the content of Na2SiF6 powder is 5wt%, the content of Si powder is 5wt%, the total content of borax and B4C powder is 0.02wt%, and the content of Y powder is 0.02wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for surface modification of molybdenum alloy.

[0248] B1. The molybdenum alloy matrix is ​​buried in the 1# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the molybdenum alloy matrix is ​​4 mm;

[0249] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 950° C., and the heating time was 6 hours. The 1# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a pre-treated coating sample of a molten salt non-electrolytic modified coating was obtained on the surface of the molybdenum alloy.

[0250] B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating in the 2# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the pre-treated coating sample is 4 mm;

[0251] B4. Using a muffle furnace, a thermocouple as a heat source, and controlling the heating temperature to 1000°C for a heating time of 6 hours, the 2# mixed powder for surface modification of the molybdenum alloy is prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a two-step molten salt non-electrolytic modified coating is obtained on the surface of the molybdenum alloy. The study shows that no B, Hf, or Y modifying elements are found in the coating.

[0252] Comparative Example 6

[0253] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum surface comprises the following steps:

[0254] B0. Use 400-2000 mesh sandpaper to grind the molybdenum substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0255] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders using a grinding mortar;

[0256] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y2O3 powders are all 3 to 60 μm;

[0257] S2. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders were placed in a ball mill and mixed to obtain 1# mixed powder. The ball milling speed was 200 rpm, the ball milling time was 1.5 h, and the forward and reverse rotations were 0.75 h each;

[0258] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and Y2O3 powders were placed in a ball mill and milled to obtain a 2# mixed powder. The ball milling speed was 200 rpm, the ball milling time was 2 h, and the forward and reverse rotations were 1 h each;

[0259] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 74wt%, the content of Na2SiF6 powder is 10wt%, the content of Si powder is 15wt%, the total content of borax and B4C powder is 1wt%, and the content of HfB2 powder is 10wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 72wt%, the content of Na2SiF6 powder is 5wt%, the content of Si powder is 5wt%, the total content of borax and B4C powder is 8wt%, and the content of Y2O3 powder is 10wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for molybdenum surface modification.

[0260] B1, burying the molybdenum substrate in the 1# mixed powder for molybdenum surface modification described in S4; the thickness of the powder for molybdenum surface modification covering the molybdenum substrate is 3 mm;

[0261] B2. Using a muffle furnace and a thermocouple as a heat source, the heating temperature is controlled to be 1000° C. and the heating time is 12 hours. The 1# mixed powder for molybdenum surface modification is prepared on a molybdenum substrate by a molten salt non-electrolytic method to obtain a pretreated coating sample of the molten salt non-electrolytic modified coating on the molybdenum surface.

[0262] B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating in the 2# mixed powder for molybdenum surface modification described in S4; the thickness of the powder for molybdenum surface modification covering the pre-treated coating sample is 5 mm;

[0263] B4, using a muffle furnace, a thermocouple as a heat source, controlling the heating temperature to 1050°C, and the heating time to 12 hours, the 2# mixed powder for molybdenum surface modification is prepared on a molybdenum substrate by a molten salt non-electrolytic method, and a two-step molten salt non-electrolytic modified coating is obtained on the molybdenum surface. Studies have shown that if the heating time is too long, the prepared coating will crack.

[0264] Comparative Example 7

[0265] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum surface comprises the following steps:

[0266] B0. Use 400-2000 mesh sandpaper to grind the molybdenum substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0267] S0. Grinding NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders using a grinding mortar;

[0268] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and YCl3 powders are all 3 to 60 μm;

[0269] S2. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders were placed in a ball mill and mixed to obtain 1# mixed powder. The ball milling speed was 300 rpm, the ball milling time was 3 h, and the forward and reverse rotations were 1.5 h each;

[0270] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and YCl3 powders were placed in a ball mill and mixed to obtain 2# mixed powder. The ball milling speed was 300 rpm, the ball milling time was 1.5 h, and the forward and reverse rotations were 0.75 h each;

[0271] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 68wt%, the content of Na2SiF6 powder is 15wt%, the content of Si powder is 5wt%, the total content of borax and B4C powder is 2wt%, and the content of HfB2 powder is 10wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 63wt%, the content of Na2SiF6 powder is 15wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 10wt%, and the content of YCl3 powder is 2wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for molybdenum surface modification.

[0272] B1, burying the molybdenum substrate in the 1# mixed powder for molybdenum surface modification described in S4; the thickness of the powder for molybdenum surface modification covering the molybdenum substrate is 4.5 mm;

[0273] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 750° C., and the heating time was 4 hours. The 1# mixed powder for surface modification of molybdenum was prepared on a molybdenum substrate by a molten salt non-electrolytic method, and a pre-treated coating sample of the molten salt non-electrolytic modified coating was obtained on the molybdenum surface.

[0274] B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating in the 2# mixed powder for molybdenum surface modification described in S4; the thickness of the powder for molybdenum surface modification covering the pre-treated coating sample is 5 mm;

[0275] B4. Using a muffle furnace, a thermocouple as a heat source, and controlling the heating temperature to 750°C for 4 hours, the 2# mixed powder for molybdenum surface modification was prepared on a molybdenum substrate by a molten salt non-electrolytic method to obtain a two-step molten salt non-electrolytic modified coating on the molybdenum surface. Studies have shown that the preparation temperature is too low, and no B, Si, Hf, or Y elements are found on the sample surface.

[0276] Comparative Example 8

[0277] A method for preparing a modified MoSi2 anti-oxidation coating on a molybdenum alloy surface comprises the following steps:

[0278] B0. Use 400-2000 mesh sandpaper to grind the molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for standby use;

[0279] S0. NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders were ground using a grinding mortar;

[0280] S1. Take NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders for use; the particle sizes of NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C, HfB2 and Y powders are all 3 to 60 μm;

[0281] S2. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and HfB2 powders were placed in a ball mill and mixed to obtain 1# mixed powder. The ball milling speed was 300 rpm, the ball milling time was 1.5 h, and the forward and reverse rotations were 0.75 h each;

[0282] S3. The NaCl-KCl-NaF, Na2SiF6, Si, borax, B4C and Y powders were placed in a ball mill and mixed to obtain 2# mixed powder. The ball milling speed was 150 rpm, the ball milling time was 3 h, and the forward and reverse rotations were 1.5 h each;

[0283] In the S4.1# mixed powder, the content of NaCl-KCl-NaF powder is 75wt%, the content of Na2SiF6 powder is 5wt%, the content of Si powder is 10wt%, the total content of borax and B4C powder is 5wt%, and the content of HfB2 powder is 5wt%. In the 2# mixed powder, the content of NaCl-KCl-NaF powder is 65wt%, the content of Na2SiF6 powder is 10wt%, the content of Si powder is 15wt%, the total content of borax and B4C powder is 5wt%, and the content of Y powder is 5wt%. The 1# mixed powder and the 2# mixed powder are placed in a dryer and dried to obtain powders for surface modification of molybdenum alloy.

[0284] B1. The molybdenum alloy matrix is ​​buried in the 1# mixed powder; the thickness of the powder for surface modification of the molybdenum alloy covering the molybdenum alloy matrix is ​​4 mm;

[0285] B2. A muffle furnace was used with a thermocouple as a heat source, the heating temperature was controlled to be 1200° C., and the heating time was 2 h. The 1# mixed powder for surface modification of the molybdenum alloy was prepared on a molybdenum alloy substrate by a molten salt non-electrolytic method, and a pre-treated coating sample of the molten salt non-electrolytic method modified coating was obtained on the surface of the molybdenum alloy.

[0286] B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating in the 2# mixed powder; the thickness of the powder for surface modification of molybdenum alloy covering the pre-treated coating sample is 4 mm;

[0287] B4, using a muffle furnace, a thermocouple as a heat source, controlling the heating temperature to 1200°C, and the heating time to 2 hours, the 2# mixed powder for surface modification of the molybdenum alloy is prepared on the molybdenum alloy substrate by a molten salt non-electrolytic method, and a two-step molten salt non-electrolytic modified coating is obtained on the molybdenum alloy surface. Studies have shown that excessively high heating temperatures lead to cracking of the coating.

[0288] The present invention selects modified 1# mixed powder: at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax / B4C powder, and HfB2 powder; modified 2# mixed powder: at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax / B4C powder, and Y / Y2O3 / YCl3 powder. The Mo-Si-B-Hf-Y composite coating is prepared on the surface of the molybdenum alloy by a two-step molten salt non-electrolytic process, wherein MoSi2 as the basic material of the coating can ensure the antioxidant performance of the composite coating, and adding an appropriate amount of B element, Hf element and Y element can further improve the antioxidant performance of the coating, and finally the coating has good antioxidant performance, good density and durability, which can meet the application of molybdenum or molybdenum alloy in high temperature service environment.

[0289] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a powder for surface modification of molybdenum or molybdenum alloy, characterized in that: The steps include: S1. Take at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax / B4C powder, HfB2 powder, Y / Y2O3 / YCl3 powder for standby; S2. The NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, at least one of borax and B4C powder, and HfB2 powder were placed in a ball mill and mixed to obtain a mixed powder #1, the ball milling speed was 150 to 300 rpm, and the ball milling time was 1.5 to 3.5 h; S3. The NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, at least one of borax / B4C powder, at least one of Y / Y2O3 / YCl3 powder was placed in a ball mill and mixed to obtain a 2# mixed powder, the ball milling speed was 150 to 300 rpm, and the ball milling time was 1.5 to 3.5 h; S4. Place the 1# mixed powder and the 2# mixed powder in a dryer to dry them respectively, to obtain powders for surface modification of molybdenum or molybdenum alloy.

2. The method for preparing a powder for surface modification of molybdenum or molybdenum alloy according to claim 1, characterized in that: Before step S1, the method further includes: S0. Use a grinding mortar to grind at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax / B4C powder, HfB2 powder, and Y / Y2O3 / YCl3 powder.

3. The method for preparing a powder for surface modification of molybdenum or molybdenum alloy according to claim 1, characterized in that: In the step S1, the particle sizes of at least one of NaCl-KCl-NaF powder, Na2SiF6 powder, Si powder, borax / B4C powder, HfB2 powder, and Y / Y2O3 / YCl3 powder are all 3 to 60 μm.

4. The method for preparing a powder for surface modification of molybdenum or molybdenum alloy according to claim 1, characterized in that: In the steps S2 and S3, the ball milling is performed in forward and reverse directions, and the forward and reverse directions have the same time.

5. The method for preparing the powder for surface modification of molybdenum or molybdenum alloy according to claim 1, characterized in that: In the step S4, in the 1# mixed powder for surface modification of molybdenum or molybdenum alloy, the content of NaCl-KCl-NaF powder is 35-94.7wt%, the content of Na2SiF6 powder is 0.1-20wt%, the content of Si powder is 5-20wt%, the content of at least one of borax and B4C powder is 0.1-10wt%, and the content of HfB2 powder is 0.1-15wt%; in the 2# mixed powder for surface modification of molybdenum or molybdenum alloy, the content of NaCl-KCl-NaF powder is 30-94.7wt%, the content of Na2SiF6 powder is 0.1-20wt%, the content of Si powder is 5-20wt%, the content of at least one of borax and B4C powder is 0.1-10wt%, and the content of at least one of Y / Y2O3 / YCl3 powder is 0.1-20wt%.

6. A powder for surface modification of molybdenum or molybdenum alloy, characterized in that: The powder is prepared by the method for preparing the powder for surface modification of molybdenum or molybdenum alloy according to any one of claims 1 to 5.

7. A method for preparing a modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy, characterized in that: The steps include: B1. embedding a molybdenum or molybdenum alloy matrix into the 1# mixed powder or 2# mixed powder in the above-mentioned powder for surface modification of molybdenum or molybdenum alloy; B2. Controlling the heating temperature and heating time to obtain a pre-treated coating sample of a molten salt non-electrolytic modified coating on the surface of molybdenum or molybdenum alloy; B3, burying the pre-treated coating sample of the molten salt non-electrolytic modified coating into another mixed powder of the above-mentioned powder for surface modification of molybdenum or molybdenum alloy; B4. Control the heating temperature and heating time to obtain a two-step molten salt non-electrolytic modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy.

8. The method for preparing the modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy according to claim 7, characterized in that: Before step B1, the method further includes: B0. Use sandpaper to grind the molybdenum or molybdenum alloy substrate, then use anhydrous ethanol to clean it, and then dry it for use.

9. The method for preparing the modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy according to claim 7, characterized in that: In the steps B1 and B3, the thickness of the powder for surface modification of molybdenum or molybdenum alloy covering the molybdenum or molybdenum alloy substrate is ≥3 mm.

10. The method for preparing the modified MoSi2 anti-oxidation coating on the surface of molybdenum or molybdenum alloy according to claim 7, characterized in that: In the steps B2 and B4, the heating temperature is 850-1100° C. and the heating time is 2-8 hours.

Citation Information

Cited By

  • Preparation method of anti-oxidation coating on surfaces of molybdenum and molybdenum alloy

    CN120330657A